Determining a global mid-upper arm circumference cut-off to assess underweight in adults (men and non-pregnant women) - Tang, Alice M.; Chung, Mei; Dong, Kimberly R.; Bahwere, Paluku; Bose, Kaushik; Nguyen, Phuong Hong (Cambridge University Press, 2020)
To determine if a global mid-upper arm circumference (MUAC) cut-off can be established to classify underweight in adults (men and non-pregnant women).We conducted an individual participant data meta-analysis (IPDMA) to explore the sensitivity (SENS) and specificity (SPEC) of various MUAC cut-offs for identifying underweight among adults (defined as BMI < 18·5 kg/m2). Measures of diagnostic accuracy were determined every 0·5 cm across MUAC values from 19·0 to 26·5 cm. A bivariate random effects model was used to jointly estimate SENS and SPEC while accounting for heterogeneity between studies. Various subgroup analyses were performed.Twenty datasets from Africa, South Asia, Southeast Asia, North America and South America were included.All eligible participants from the original datasets were included.The total sample size was 13 835. Mean age was 32·6 years and 65 % of participants were female. Mean MUAC was 25·7 cm, and 28 % of all participants had low BMI (<18·5 kg/m2). The area under the receiver operating characteristic curve for the pooled dataset was 0·91 (range across studies 0·61–0·98). Results showed that MUAC cut-offs in the range of ≤23·5 to ≤25·0 cm could serve as an appropriate screening indicator for underweight.MUAC is highly discriminatory in its ability to distinguish adults with BMI above and below 18·5 kg/m2. This IPDMA is the first step towards determining a global MUAC cut-off for adults. Validation studies are needed to determine whether the proposed MUAC cut-off of 24 cm is associated with poor functional outcomes.